Effect of regrowth age and climate on the chemical composition of Cenchrus purpureus in degraded ecosystems of Cuba - Méndez-Martínez, Yuniel (2020)
The objective of this work was to determine the effect of age and climate on the chemical composition of Cenchrus purpureus in degraded ecosystems of Cuba. An experiment was carried out in two well-defined periods: slightly rainy (January to April) and rainy (July to October). The treatments (regrowth ages: 30, 45, 60, 75, 90 105 days) were distributed in a randomized block design with four replicas. The structural constituents of the cell wall, minerals (calcium and phosphorus), and digestibility of dry and organic matter were determined. The neutral detergent fiber showed a behavior defined by the climatic season (72.37%) in rains and 69.67% in few rains). The elements of the climate showed a high relationship with the chemical composition and linear regression models were adjusted with high coefficients of determination, greater than 0.71 in the two periods evaluated; the rainfall and maximum temperature variables were the ones that provided the greatest adjustments. With the increase in age, the quality of the plant decreased, and of climatic factors, rainfall and maximum temperature are those that most affect the nutritional quality of the plant.